PERBEDAAN ABNORMAL RETURN SEBELUM DAN SESUDAH PENGUMUMAN PENURUNAN HARGA BBM - Uchi Laksmi, Ni Kadek; Dwi Ratnadi, Ni Made (E-Jurnal Akuntansi; Vol 13 No 3 (2015), 2015)
Stock price movements are influenced by the development of environmental and  macroeconomic activities. This is reflected by the market reaction. Market reaction can be measured by abnormal return. This research has a purpose to determine differences between in abnormal return before and after the reduction of Fuel Oil price on 1st January 2015 in the transportation sector companies which listed on the Indonesia Stock Exchange period 2014-2015. The sample determined by utilizing purposive sampling technique, therefore as many as 33 of observation samples. This research includes event study with the observation period is 11 working days. Data collected by observation nonparticipant. Data will be tested by t-test and the result showed thewe was no difference of abnormal return between before and after the announcement of the reduction in fuel prices.
Keywords: announcement of the reduction in fuel oil prices, abnormal return, event study